2009
DOI: 10.1063/1.3098141
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular energy transfer and the driving mechanisms for large-amplitude collective motions of clusters

Abstract: This paper uncovers novel and specific dynamical mechanisms that initiate large-amplitude collective motions in polyatomic molecules. These mechanisms are understood in terms of intramolecular energy transfer between modes and driving forces. Structural transition dynamics of a six-atom cluster between a symmetric and an elongated isomer is highlighted as an illustrative example of what is a general message. First, we introduce a general method of hyperspherical mode analysis to analyze the energy transfer amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 72 publications
(164 reference statements)
0
24
0
Order By: Relevance
“…Moreover, recent studies 75,[77][78][79] have suggested that one can utilize these pathways of energy transfer to induce molecular reactions by selectively activating specific degrees of freedom. Since the hyperspherical coordinates give a concise and universal expression for the kinetic energy of many-atom systems, [48][49][50][51][52][53][54][55][56][57][58]70,71 our present approach is indeed suitable to the study of energy transfer among internal degrees of freedom. By taking this advantage, we identify characteristic pathways of energy transfer that are responsible for the onset of structural transitions of the cluster between oblate and prolate isomers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, recent studies 75,[77][78][79] have suggested that one can utilize these pathways of energy transfer to induce molecular reactions by selectively activating specific degrees of freedom. Since the hyperspherical coordinates give a concise and universal expression for the kinetic energy of many-atom systems, [48][49][50][51][52][53][54][55][56][57][58]70,71 our present approach is indeed suitable to the study of energy transfer among internal degrees of freedom. By taking this advantage, we identify characteristic pathways of energy transfer that are responsible for the onset of structural transitions of the cluster between oblate and prolate isomers.…”
Section: Introductionmentioning
confidence: 99%
“…Three of the hyperangular degrees of freedom correspond to twisting motions, and the remaining 3n − 12 hyperangular degrees of freedom correspond to shearing motions. 71 Activations of the twisting and shearing motions induce dynamical forces called the internal centrifugal forces. 70,71 The internal centrifugal force originating from the twisting motions has an effect of breaking the symmetry between two of the gyration radii.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coarse variable of the (approximate) 0th mode, which is the average angle of the pendula, corresponds to the angle of the frame defined by the radius of gyration in our molecular studies. [40][41][42] This variable is a global and slow variable and it plays an important role as the reactive coordinate for our DNA work. Moreover, this reactive mode forms a nearly 0:1 resonance with any other mode, each of which has an O(1) frequency.…”
Section: Introductionmentioning
confidence: 99%